Manfaat Herbal Pegagan (Centella Asiatica (L.)) dalam Membantu Mencegah Alzheimer - Yelfi Anwar; Regina Regina; Dias Septiana Sari; Yofie Aldo Aditya; Syifa Alifia Indriani; Silvy Widya Rahmi; Diajeng Para Mitha (Pusat Riset dan Inovasi Nasional, 2024)
This community service aims to provide information about the role of Gotu kola extract (Centella asiatica) as a neural antioxidant and mitoprotective in the context of helping reduce symptoms of Alzheimer's disease. Alzheimer's, a form of dementia common in old age, still has no effective treatment after more than a hundred years of research. Gotu kola extract has been traditionally known in Asia as a cognitive-enhancing drug and has antioxidant and mitoprotective properties that can revitalize nerve and brain cells. Through the community service program, we organized a webinar on the benefits of Gotu Kola herbs in helping prevent Alzheimer's disease for students of the University of 17 August 1945 Jakarta and the general public in North Jakarta. The results of this activity showed a positive response from participants, with 42 participants from various backgrounds attending the webinar.